Digitalizacija slovenskega sodstva danes ter izzivi in rešitve za jutri - Brezovar, Rado (Podjetje in delo, 2022)
E-justice in Slovene judiciary is considered one of the most important driving forces towards efficient administration of the Slovene judiciary. The term e-justice means more than just the use of ICT in the judiciary. It is a set of legal and organisational measures that function in close cooperation with the technical potentials. Synergies among all three (legal, organisational, and technical) components are constantly sought and they are not limited to the closed judicial community. They are opened to all beneficiaries of judicial services.
Keywords: business intelligence; e-case management systems; E-justice; e-sodstvo; e-vpisniki; interoperability; interoperabilnost; poslovno obveščanje